Thai food in Malaysia: diagnosing patrons and restaurant operators’ acceptance levels / Nurul Aishah @ N Zakaria... [et al.] - Zakaria, Nurul Aishah @ N; Mohd Zahari, Mohd Salehuddin; Mat Noor, Syuhirdy; Othman, Zulhan (2009)
In the last twenty years Thai food has been making waves in Malaysia. This is not to generalize, but the number of restaurants offering Thai food in this country is on the rise. Thai food is flourishing not only in the large cities but small town even in secluded areas. Most restaurants are seen incorporate this cuisine in their menus. Restaurants which sell Thai food are quite packed with customers especially during dinner time. This empirical study investigated to what extent the local customers and restaurant operators accept Thai food. In addition, this study also evaluated any changes in customers’ eating patterns of local cuisines. Customers and restaurant operators in three Malaysia nothem states (Perlis, Kedah and Penang) were selected as a sample. One notable finding was that respondents saw a trend towards Thai foods which are becoming well accepted in this country. Nevertheless, despite the increasingly popularity of Thai food it was not to the extent of outshining the local food. Thai foods were found to be not consumed everyday by the local people, but rather as an option or alternative or as part of leisure dining. Another interesting issue and in fact the most remarkable finding of this study was that respondents seemed to agree that Thai food is more popular and internationally accepted than Malaysian food. This indication has significant implications for the related